Effect of a second treatment of prostaglandin F2α during the Ovsynch program on fixed‐time artificial insemination conception rates and luteolysis in split‐calving, pasture‐fed dairy cows. Issue 5 (18th March 2020) - Rheinberger, JM; Colson, DD; Beggs, DS; Mansell, PD; Stevenson, MA; Rheinberger, RJ; Pyman, MF
Abstract : Objective: To compare fixed‐time artificial insemination (FTAI) conception rates and serum progesterone concentrations at the time of FTAI for cows treated with the original Ovsynch program (OV) with those treated with a modified Ovsynch (MO) program. Design: This was a randomised clinical trial. Methods: The study used five split‐calving, pasture‐based dairy herds in Southwest Victoria, Australia. Controls (n = 851) received the OV program: day 0 gonadotropin‐releasing hormone, day 7 prostaglandin F2α (PGF), day 9 gonadotropin‐releasing hormone and FTAI at day 10. The treatment group (n = 852) received a MO program with an additional prostaglandin injection on day 8. Subsets of cows from each group were sampled for blood progesterone at the time of FTAI. Results: The treatment group demonstrated FTAI conception rates that were 7% (95% confidence interval 2%–12%) greater than the control group. After adjusting for the effect of age, days in milk at Mating Start Date and herd, the odds of conception using FTAI was 1.36 (95% confidence interval 1.12–1.66) times greater for treatment group cows compared with control group cows. The variability of serum progesterone concentrations at the time of FTAI was significantly less for treatment group cows compared with control group cows. Conclusion: For Holstein‐Friesian and Holstein‐Friesian cross‐bred cows managed in pasture‐based dairy herds in southern Australia, a MO protocol, including a second injection of prostaglandin F2α on day 8, increased FTAI conception rates compared with cows receiving the OV protocol.